Analisis Kualitas Website Perpustakaan Menggunakan Metode Webqual 4.0 - Mahida Hanifah Rahmadini; Asif Faroqi; Anita Wulansari (STMIK Banjarbaru, 2022)
The emergence of several technical problems related to the availability of adequate functional features, led to the need for an analysis of the website performance of the UPT